2021
DOI: 10.3390/jof7110939
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Role of Dark Septate Endophytes in the Plant Resistance to Abiotic and Biotic Stresses

Abstract: Endophytic fungi have been studied in recent decades to understand how they interact with their hosts, the types of relationships they establish, and the potential effects of this interaction. Dark septate endophytes (DSE) are isolated from healthy plants and form melanised structures in the roots, including inter- and intracellular hyphae and microsclerotia, causing low host specificity and covering a wide geographic range. Many studies have revealed beneficial relationships between DSE and their hosts, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 142 publications
5
45
0
Order By: Relevance
“…Pb mainly accumulates in the root system of maize and the phytotoxicity of Pb to the shoot is alleviated [75]. One of the reasons for that DSE colonization increases plant growth under metal addition is that DSE enhances metal tolerance and improves plant growth by altering metal repartitioning into the root and shoot [19,48,52,54]. In our results, we found that more Cd accumulated in maize with increasing concentration of Cd, and the Cd content in roots was higher than that in the shoots.…”
Section: The Effects Of Dse Inoculation On Growth and CD Distribution Of Maizesupporting
confidence: 50%
See 1 more Smart Citation
“…Pb mainly accumulates in the root system of maize and the phytotoxicity of Pb to the shoot is alleviated [75]. One of the reasons for that DSE colonization increases plant growth under metal addition is that DSE enhances metal tolerance and improves plant growth by altering metal repartitioning into the root and shoot [19,48,52,54]. In our results, we found that more Cd accumulated in maize with increasing concentration of Cd, and the Cd content in roots was higher than that in the shoots.…”
Section: The Effects Of Dse Inoculation On Growth and CD Distribution Of Maizesupporting
confidence: 50%
“…DSEs extend mucilaginous hyphae to promote the transportation of water and nutrients in arid environments, helping rice and sorghum survive in arid environments and improving their drought resistance [46,47]. The DSE-host interaction is crucial to plant survival [48]. In particular, the DSE strain, Exophiala pisciphila, which was isolated from heavy metal contaminated soil, has a strong tolerance to heavy metals under in vitro culture conditions [49].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses show that A. tellustris can diminish the nutrients and space available to both terrestrial pathogens. These results appear to indicate that DSE have an important role in diminishing the nutritional and spatial resources available to terrestrial plant pathogens, using different mechanisms of action, as mentioned by Santos et al [ 56 ]. The present research suggests that endophytic fungi, such as A. tellustris , may have a role in the induction of a plant’s defensive responses, such as systemic acquired resistance (SAR) and induced systemic resistance (ISR).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, S. indica enhances salt tolerance in its host A. thaliana via sodium (Na) and potassium (K) efflux transporters, thereby decreasing the Na content in the plant (Lanza et al ., 2019). Similarly, some DSE fungi are thought to improve drought resistance and salt tolerance in different plant species (Santos et al ., 2021). Under current global change scenarios, the abundance of plant pathogens in soil is predicted to increase (Delgado‐Baquerizo et al ., 2020), implying that plant protection by endophytic mycorrhizal‐like fungi could improve plant adaptation to increased disease pressure.…”
Section: Will Mycorrhiza‐like Associations Help Plants Adapt To Globa...mentioning
confidence: 99%